A mãe e o mar: imagens do feminino no poema Mar absoluto, de Cecília Meireles - Gonçalves, Giselli Renata (2012)
In the task to investigate the functioning of psyche, it fits to Psychology to stabilish a dialogue with different fields where the soul finds expression possibilities. In such case, the poetical art, whose psychological meaning was already salient for Jung, seems to constitute a privileged field for manifestation of symbolic contents. Our research consists of examining the symbols related to Feminine Archetypal expressed by the poem Mar Absoluto (Absolute Sea), authored by Cecilia Meireles. We aim to understand which aspects of this archetype are expressed by its writing, how they are expressed and its imagistic contents. We adopt a method of qualitative analysis, based on ontologic and epistemologic concepts of the Jungian paradigm. The symbolic images were submitted to the analysis method proposed by Penna (2009), called archetypal symbolic process, which aims to understand and assimilate the meaning of the symbol. To do so, we use the process of symbolic amplification, which consists of widening the context of images, relating it to mythology, folklore and art, aiming to place it in the panorama of universal subjects of the human experience. Thus, we hope "to translate" such images in concepts, and possibly to know its meanings in depth. The analysis results show that the symbols expressed by the poem join both polarities of the maternal archetype, that is, they refer to the Good-Bad Mother. The sea appears experienced as a Great Mother Sea